Equilibrium Isotherms and Kinetics Modelling for an Efficient Removal of 4-Chloro-2-Methoxyphenol From Aqueous Solution Using Optimal Activated Carbon - Zaharaddeen N. Garba; I. Ibrahim; Afidah Abdul Rahim (Hamadan University of Medical Sciences, 2021)
A surface area of 1085.92 m2 /g and a monolayer adsorption capacity of 497.66 mg/g were obtained from the optimum activated carbon derived using Prosopis africana seed hulls (PASH-AC) at the activation temperature of 795°C, activation time of 62 minutes, and impregnation ratio of 2.45. Five different forms of the linearized Langmuir equations along with two other models (Freundlich and Temkin) were tested on the adsorption data. The best adsorption model was selected using correlation coefficient (R2 ) and chi-square (χ2 ) was used for assessing the validity of each isotherm model. Langmuir-2 along and pseudo-second-order models were found to be the most suitable model for describing the equilibrium and kinetic processes, respectively.